2021
DOI: 10.1186/s12872-020-01830-5
|View full text |Cite
|
Sign up to set email alerts
|

Time to peak bilirubin concentration and advanced AKI were associated with increased mortality in rheumatic heart valve replacement surgery patients with severe postoperative hyperbilirubinemia: a retrospective cohort study

Abstract: Background Hyperbilirubinemia after heart valve surgery (HVS) with cardiopulmonary bypass is frequently observed and associated with worse outcomes. We investigated the characteristics and prognosis of patients with severe hyperbilirubinemia after HVS for rheumatic heart disease (RHD) to identify the clinical outcomes and potential risk factors. Methods Between 2015 and 2018, patients who underwent HVS in the cardiac surgery intensive care unit of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 42 publications
(53 reference statements)
0
9
0
Order By: Relevance
“…Most studies were positive about the correlation between hyperbilirubinemia and postoperative complications as well as with adverse events (3,5,(10)(11)(12)(16)(17)(18). Hyperbilirubinemia after cardiac surgery (especially after cardiopulmonary bypass) is a risk factor for postoperative respiratory(8), circulatory (12,18), urinary (19,20), gastrointestinal complications(21) and hospital mortality. In this study, incidences of pulmonary infection, new acute renal failure, continuous renal replacement therapy, perioperative myocardial infarction and other related complications in the hyperbilirubinemia group were elevated, while incidences of MODS and hospital mortality were higher than those of the normal serum total bilirubin group, with statistically signi cant differences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies were positive about the correlation between hyperbilirubinemia and postoperative complications as well as with adverse events (3,5,(10)(11)(12)(16)(17)(18). Hyperbilirubinemia after cardiac surgery (especially after cardiopulmonary bypass) is a risk factor for postoperative respiratory(8), circulatory (12,18), urinary (19,20), gastrointestinal complications(21) and hospital mortality. In this study, incidences of pulmonary infection, new acute renal failure, continuous renal replacement therapy, perioperative myocardial infarction and other related complications in the hyperbilirubinemia group were elevated, while incidences of MODS and hospital mortality were higher than those of the normal serum total bilirubin group, with statistically signi cant differences.…”
Section: Discussionmentioning
confidence: 99%
“…Prolonged bilirubin peak time in patients with hyperbilirubinemia is an independent predictor of death. Chen et al, Sharma et al and others reported that early jaundice after cardiac surgery is mostly transient, and is mainly caused by surgical strikes, while late and persistent hyperbilirubinemia (lasting for more than 5 days after operation) may be related to cardiac failure (12,17,18) or septicemia, leading to acute liver failure, with rapidly elevated in-hospital mortality rates (2,11,20). Farag et al reported that patients with bilirubin peak time more than 3.5 days and peak value exceeding 91.5 µmol/L had signi cantly higher mortality rates while patients with bilirubin peak value exceeding 436.1 µmol/L had mortality rates above 99%(16).…”
Section: Discussionmentioning
confidence: 99%
“…Most studies were positive about the correlation between hyperbilirubinemia and postoperative complications as well as with adverse events [ 4 , 6 , 11 , 17 , 18 , 22 24 ], which embodied the importance of this study. Hyperbilirubinemia after cardiac surgery (especially after cardiopulmonary bypass) is a risk factor for postoperative respiratory [ 9 ], circulatory [ 18 , 24 ], urinary [ 25 , 26 ], gastrointestinal complications [ 27 ] and associated with in-hospital mortality [ 2 – 7 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms through which hyperbilirubinemia leads to complications and poor prognosis are complex, and have not been fully elucidated. Elevated bilirubin concentrations can trigger cell oxidative stress, induce apoptosis [ 23 ], and participate in a variety of pathological processes, including respiratory dysfunction, thrombocytopenia [ 25 ], renal tubular epithelial cell damage [ 26 , 28 ], neural cell differentiation and myelination inhibition [ 29 ]. In addition, persistent hyperbilirubinemia is only a manifestation of a potential disease, such as persistent low cardiac output syndrome, rather than a direct cause of death [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…The mortality of patients with AKI is quite high, particularly in those with severe AKI who require dialysis; the mortality can exceed 50% [3]. Some clinical indicators, such as platelet, bilirubin, phosphate, Sequential Organ Failure Assessment (SOFA) score, and Acute Physiology and Chronic Health Evaluation II (APACHE II) score, have reportedly been related to the prognosis of critically ill patients with AKI [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%